Aid, Infrastructure, and FDI: Assessing the Transmission Channel with a New Index of Infrastructure. (February 2016) - Donaubauer, Julian; Meyer, Birgit; Nunnenkamp, Peter
Highlights: We analyze whether foreign aid helps recipient countries to attract FDI. Our estimation approach accounts for dependencies between aid, infrastructure, and FDI. Targeted aid promotes FDI indirectly through the infrastructure channel. Aid in infrastructure also impacts directly on FDI. Summary: Official development assistance (ODA) and foreign direct investment (FDI) are widely perceived to be alternative means of supplementing domestic savings and promoting economic development in low- and middle-income countries. However, possible complementarities of aid and FDI have received limited attention so far. It remains open to debate whether aid could render recipient countries more attractive to FDI by removing specific bottlenecks that prevent higher FDI inflows. In particular, we raise the hypothesis that aid specifically targeted at economic infrastructure helps developing countries attract higher FDI inflows through improving their endowment with infrastructure in transportation, communication, energy, and finance. By performing 3SLS estimations we explicitly account for dependencies between three structural equations on the allocation of sector-specific aid, the determinants of infrastructure, and the determinants of FDI. We find strong and robust evidence that aid in infrastructure is effective in improving the recipient countries' endowment with infrastructure. In sharp contrast, other aid is not effective in improving infrastructure. Infrastructure consistently proves to be an important determinant of developing countries' attractiveness to FDI. Consequently, only targeted aid promotes FDI indirectly through the infrastructure channel. In addition, aid in infrastructure has direct effects on FDI. It appears that foreign investors anticipate longer term effects of aid on the country's endowment with infrastructure and expect aid-financed infrastructure to serve them particularly well.